HÛD SÛRESINDEKI HABERÎ VE INŞAÎ CÜMLELER (BELAĞÎ VE NAHVÎ BIR ÇALIŞMA) - MAAROOF, BAHJAT YOUSIF (Fırat Üniveristesi, 2021)
Bu çalışmada Hud Suresinin ayetleri haber ve inşa cümleleri bağlamında analiz edilmektedir. Çalışmada haber cümlesi izah edilmiş, onun nahivciler ve belagatçılar nazarında nasıl anlaşıldığına, amaçlarına, kısımlarına ve onu te'kit eden ifadelere değinilmiştir. Ayrıca haber cümlesinin mecazi manaları olan terğîb (teşvik), terhîb (korkutma), ta'lîl (sebep bildirme), nasihat, irşad, imtinân(minnettarlık), va'îd (uyarı) ve tehdid gibi konular işlenmiştir. Bunun yanı sıra talebî inşa cümleleri izah edilmiş ve anlamı üzerinde durulmuştur. Bu tür cümlelerin istifham, emir, nehiy ve dua gibi üslupları ele alınmıştır. Hud suresinde, zikri geçen tüm bu cümle çeşitleri etrafında şekillenen ayetler nahiv ve belagat açısından analiz edilmiştir. Suredeki ibareler kasem, temenni, taaccub, medih ve zemm anlamları içermeleri bakımından belagat ve nahiv açısından da tahlil edilmiştir.

In this study, the verses of Surah Hud are analyzed in the context of news and construction sentences. In the study, the news sentence is explained, how it is understood in the eyes of grammarians and rhetoricians, its aims, parts and the statements that support it are mentioned. In addition, the metaphorical meanings of the news sentence, such as terghib (encouragement), terhib (intimidation), ta'lil (giving reason), rede, guidance, imtinan (gratitude), va'îd (warning), and threats were discussed. In addition, the requestingial construction sentences were explained and their meaning was emphasized. The styles of such sentences such as question, order, forbidding and praying were discussed. In Surah Hud, the verses formed around all these sentence types mentioned above were analyzed in terms of grammar and rhetoric. The phrases in the Surah have been analyzed in terms of rhetoric and grammar in terms of containing the meanings of oath, wish, exclamation, lauding and condemnation.
News and construction sentences in surah Hud (A grammatical and rhetorical research)
Keywords: Din